Community-Engaged Research in Teaching Research Methods (Revista de sociología clínica, 2025)
This article presents a community-engaged project integrated into a research methods course. The goal of the course was to engage students in research on a transitional housing program for homeless veterans and develop their understanding of veteran homelessness. While students learned the basic concepts, theoretical paradigms, and methods of qualitative research from assigned readings, class lectures, and discussions, they engaged in research activities such as data collection, analysis, and dissemination in real world settings. Toward the end of the semester, the students in the course shared their research findings and recommendations for further improvement with the program stakeholders. The research outcomes were utilized to support the program development. During the research process, both student researchers and community partners gained benefits by building mutual trust and creating positive relationships. The students who completed the community-engaged project demonstrated greater knowledge of veteran homelessness and suggested ways to help them integrate back into society.